Hedging portfolios with short ETFs - Thorsten Michalik; Leo Schubert (Colegio de Economistas de A Coru\~na, 2009)
Fund Management today uses the active and passive way to construct a portfolio. Exchange Traded Funds (ETFs) are cheap instruments to cover the passive managed part of the investment. ETFs exist for stock-, bond- and commodity markets. In most cases the underlying of an ETF is an Index. Besides the investment in ETFs, for some markets, short ETFs are listed. Short ETFs allow funds manager to earn in bearish markets and therefore, short ETFs offer a competitive hedging possibility. To get some insights in the value of short ETF as instrument for 'perfect' hedging, empirical data of the German stock index DAX are used. Obviously, using short ETF for hedging cannot completely neutralize losses of the underlying instrument. The 'cross' hedge of an individual portfolio by ShortDAX ETF depicted a strong risk reduction. As risk measures, the variance, the absolute deviation and some different target-shortfall probabilities are applied. To find efficient portfolios for the cross hedge, two algorithms were developed, which need no linear or mixed integer optimization software.
Keywords: 330; Portfolio Optimization; Hedging; Insurance and Immunization of portfolios; short Exchange Traded Funds (ETFs); Mean - Absolute deviation Portfolios; Mean - Target-Shortfall-Probability Portfolios